Neotectonics of mainland Portugal: state of the art and future perspectives - Cabral, J. (Journal of Iberian Geology, 2012)
This paper presents a synthesis of the neotectonic studies performed in mainland Portugal that address the “recent” (post Piacenzian, ~3 Ma) tectonic evolution of the Portuguese territory as part of the West Iberian continental margin, specifically in regard to regional seismic hazard evaluation. The interaction of the Iberian microplate with the Nubia plate is identified as the source for the regional neotectonic deformations, which occur at relatively low rates in spite of significant historical seismic activity. In this context of low strain rates expressed by the presence of slow slip rate active faults, it is important to acquire paleoseismic data on the major seismogenic structures to characterize the large earthquakes that they generated in the past, because average recurrence intervals are much longer than the time span covered by the regional historical and instrumental period.